Can a single ammonia and water molecule enhance the formation of methanimine under tropospheric conditions?: kinetics of •CH2NH2 + O2 (+NH3/H2O) - Dash, Manas Ranjan; Ali, Mohamad Akbar (Frontiers in Chemistry, 2023)
The aminomethyl (•CH2NH2) radical is generated from the photo-oxidation of methylamine in the troposphere and is an important precursor for new particle formation. The effect of ammonia and water on the gas-phase formation of methanimine (CH2NH) from • CH2NH2+ O2 reaction is not known. Therefore, in this study, the potential energy surfaces for • CH2NH2+O2 (+NH3/H2O) were constructed using ab initio//DFT i.e., coupled-cluster theory (CCSD(T))//hybrid-density functional theory i.e., M06-2X with 6-311++G(3df,3pd) basis set. The Rice−Ramsperger−Kassel−Marcus (RRKM)/master equation (ME) simulation with Eckart's asymmetric tunneling was used to calculate the rate coefficients and branching fraction at relevant to the troposphere. The results show that 40% formation of CH2NH at low-pressure (<1 bar) and 100% formation of CH2NH2OO • at the high-pressure limit (HPL) condition. When an ammonia molecule is introduced into the reaction, the formation of CH2NH increases slightly, however, when a water molecule is introduced into the reaction, the formation of CH2NH increases from 40% to 80%. The calculated rate coefficients for • CH2NH2 +O2 (+ NH3) [1.9 × 10 -23 cm 3 molecule -1 s -1 ] is at least 12 order magnitude smaller and 6 orders magnitude smaller than CH2NH2 +O2 (+H2O) [3.3×10 -17 cm 3 molecule -1 s -1 ] than • CH2NH2 + O2 (2×10 -11 cm 3 molecule -1 s -1 at 298K) reaction. Our result is consistent with previous experimental and theoretical analysis and in good agreement with its isoelectronic analogous reaction. The work also provides a clear understanding of the formation of tropospheric carcinogenic compound i.e., hydrogen cyanide (HCN).